Head and Neck Cancer in Bali: A Retrospective Study on Patient Characteristics, Predominant Sites, and Histopathology at a Tertiary Referral Hospital - Komang Soniananda Pradnyana Putri; I Gde Ardika Nuaba; I Ketut Suanda (Open Access Indonesian Journal of Medical Reviews, 2025)
Head and neck cancers (HNCs) represent a significant global health burden, with distinct epidemiological patterns observed across different geographical regions. In Indonesia, HNCs are among the leading malignancies, yet detailed regional data, particularly from areas like Bali, remain limited. This study aimed to delineate the characteristics of HNC patients at a tertiary referral hospital in Denpasar, Bali. A retrospective descriptive study was conducted using medical records of patients diagnosed with head and neck malignancies at Prof. Dr. I.G.N.G. Ngoerah General Hospital Denpasar, between January 1st, 2021, and December 31st, 2023. Data collected included age, gender, occupation, primary tumor site, and histopathological findings. A total sampling method was employed. Descriptive statistics were used for analysis. A total of 290 patient records were analyzed. Males comprised 69% (n=201) of cases, and females 31% (n=89). The predominant age group was 45–65 years (63%, n=183). Farmers were the most common occupational group (27%, n=77). Nasopharyngeal cancer was the most prevalent malignancy, accounting for 80% (n=232) of cases. Nonkeratinizing squamous cell carcinoma was the most frequent histopathological diagnosis (80%, n=231). In conclusion, head and neck malignancies in this Balinese cohort predominantly affected middle-aged to elderly males, with farming being a common occupation. The strikingly high prevalence of nasopharyngeal cancer, primarily nonkeratinizing squamous cell carcinoma, underscores a significant regional health concern that warrants further etiological investigation and targeted public health strategies.